2016
DOI: 10.1155/2016/8631061
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune/Inflammatory Arthritis Associated Lymphomas: Who Is at Risk?

Abstract: Specific autoimmune and inflammatory rheumatic diseases have been associated with an increased risk of malignant lymphomas. Conditions such as rheumatoid arthritis (RA), primary Sjögren's syndrome (pSS), systemic lupus erythematosus (SLE), dermatomyositis, and celiac disease have been consistently linked to malignant lymphomas. Isolated cases of lymphomas associated with spondyloarthropathies and autoinflammatory diseases have also been reported. Direct association between autoimmunity and lymphomagenesis has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 103 publications
(86 reference statements)
0
22
0
Order By: Relevance
“…The etiology of RA is unclear. Previous studies suggest that RA is associated with genetic factors, infection, immunity and endocrine function (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The etiology of RA is unclear. Previous studies suggest that RA is associated with genetic factors, infection, immunity and endocrine function (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous studies have reported that inflammatory factors have an important role in the development of RA. Despite this, the etiology of this disease remains uncertain (6,12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of rheumatoid factor and involvement of the wrists and hands should not lessen clinical suspicion, particularly in patients with risk factors for cancer. In fact, DLBCL is the commonest type of lymphoma associated with rheumatoid arthritis [ 12 , 13 ]. Other chronic inflammatory conditions have also been associated with increased risk of malignant lymphomas [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, DLBCL is the commonest type of lymphoma associated with rheumatoid arthritis [ 12 , 13 ]. Other chronic inflammatory conditions have also been associated with increased risk of malignant lymphomas [ 12 ]. But the association with paraneoplastic arthritis and DLBCL is not well known.…”
Section: Discussionmentioning
confidence: 99%